SOCIAL INQUIRY FIELD WORK BASED INSTRUCTION MODEL TO IMPROVE UNDERSTANDING ENVIRONMENTAL FRIENDLY ACTIVITIES - disman, Disman; Kurniawati, Susanti; dirgantari, puspo dewi (The International Journal of Business Review (The Jobs Review), 2018)
This research is motivated by economic learning conditions that have not involved the value of sustainability. Sustainability values need to be developed in economic learning because economic activities have a great opportunity to behave in an environmentally unfriendly manner that has a broad impact. The application of sustainable values to students is realized through meaningful learning, one of which is by applying the inquiry work field learning model that emphasizes direct experience through field research. Thus this study aims to design learning models with the ADDIE approach (analysis, design, development, implementation and evaluation). To design the design of this learning model, a needs analysis was conducted and design was designed by conducting surveys, observations and literature studies on the learning model. The results of this study reveal the current conditions of economic learning, the results of the needs analysis for the preparation of learning models and the design of learning models. It is hoped that from this research, it can be an input for meaningful economic learning through direct experience that is able to foster environmentally friendly behavior in the long term.